Motivating behaviour change for safe wastewater irrigation in urban and peri-urban Ghana - Drechsel, Pay; Karg, H. (2013)
Where wastewater is used without appropriate treatment, additional safety measures such as safer irrigation practices or careful vegetable washing are required to protect farmers and consumers. Implementing such food safety interventions in the informal farming sector is not easy, as they require behaviour change. Even where appropriate and low-cost interventions have been identified, low health risk awareness is a likely adoption barrier. Where this also concerns consumers, market demand for safer crops will be low and social marketing options have to be explored to support the desired behaviour change. Based on experiences from Ghana, where wastewater irrigation is an unplanned reality in and around all cities, the necessary steps and considerations for increasing the adoption probability are outlined under a generic framework which is based on social marketing, incentive systems, awareness creation/education and supporting regulations. Any of these approaches require accompanying research of the target groups and could gain in cost-effectiveness through a more integrated approach linking e.g. handwash and vegetable washing campaigns.